New varieties and synonyms of Lupinus species (Fabaceae, Faboideae) of Northwestern Argentina - Planchuelo, Ana María (Phytotaxa, 2022)
A critical review of 28 Lupinus species names that are dubious species is presented, due that some of them are known only by the holotype, and others have several nomenclatural problems by sharing the same collection data and collector number and belonging to different taxa. After an exhaustive review of type materials and representative specimens of plants growing in the provinces of northwestern Argentina, it was possible to define the main key morphological differences, such as, the type of indumentums and the floral characteristics that define each taxon. This work presents new varieties and synonyms belonging to three taxonomic complexes: Lupinus hieronymi with five synonyms; L. burkartianus with nine synonyms and L. austrorientalis with three new varieties and a total of nine synonyms. It provides a valuable analysis of type specimens, a key for taxa identification, descriptions by morphological characters, lists of synonyms, representative specimens and categories for the PlanEAr and IUCN Red List for the species and varieties. Distribution maps, illustrations and photographs of herbarium specimens and live plants are also included.